2022
DOI: 10.1021/acs.orglett.1c03992
|View full text |Cite
|
Sign up to set email alerts
|

Rh-Catalyzed Coupling of Acrylic/Benzoic Acids with α-Diazocarbonyl Compounds: An Alternative Route for α-Pyrones and Isocoumarins

Abstract: A coupling of acrylic acids/benzoic acids with αdiazocarbonyl compounds has been realized by a combined catalytic system of rhodium catalyst and Zn(OAc) 2 additive. The presence of Zn(OAc) 2 obviously accelerates the C(sp 2 )−H activation and destructed the formation of carboxylic ester that is formed via a nucleophilic O−H insertion to metal carbenoid. The procedure featured mild reaction conditions and broad substrate scope, providing a straightforward approach to the synthesis of α-pyrones and isocoumarins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
(26 reference statements)
1
5
0
Order By: Relevance
“…Considerable attention has been focused on the carboxyl directed aryl C–H functionalization, , and the property of decarboxylation of carboxylic acids in the reaction makes the carboxyl an attractive functionality that can be tracelessly removed after the C–H activation . However, the carboxyl directed vinyl C–H activation was found to be more challenging, and the vinyl C–H functionalization using the carboxylate moiety as directing group before its decarboxylation is rarely reported . The strategy of transferring carboxyl to amide has been widely used to achieve aryl or vinyl C–H activation .…”
supporting
confidence: 57%
“…Considerable attention has been focused on the carboxyl directed aryl C–H functionalization, , and the property of decarboxylation of carboxylic acids in the reaction makes the carboxyl an attractive functionality that can be tracelessly removed after the C–H activation . However, the carboxyl directed vinyl C–H activation was found to be more challenging, and the vinyl C–H functionalization using the carboxylate moiety as directing group before its decarboxylation is rarely reported . The strategy of transferring carboxyl to amide has been widely used to achieve aryl or vinyl C–H activation .…”
supporting
confidence: 57%
“…Quite recently, Zhang and co-workers further employed α-diazocarbonyls to couple with acrylic acids under Cp*Rh­(III) catalysis to synthesize α-pyrones (Scheme ). Detailed optimization studies revealed that the addition of Zn­(OAc) 2 was essential for this transformation, which remarkablely accelerates this carboxyl-directed vinylic C–H annulation process. Electronically diverse acrylic acids reacted smoothly with a variety of α-diazocarbonyl compounds.…”
Section: Alkenyl C–h Bond Functionalization Of Alkenes Containing An ...mentioning
confidence: 99%
“…Recently, the transition-metal-catalyzed ortho C–H activation/annulation of benzoic acids has emerged as an attractive approach towards isocoumarins [ 17 18 ]. Pioneering examples relying on the Pd, Ru, and Ir-catalyzed C–H cross coupling of benzoic acids with alkenes and alkynes were realized by the groups of Miura [ 19 ], Lee [ 20 ], Ackermann [ 21 ], Zhang [ 22 ], Jiang [ 23 ], and Jeganmohan [ 24 ] et al Despite these impressive achievements, established methods often require the use of stoichiometric oxidants or harsh conditions, thus limiting their broad applicability. Consequently, it is still highly desirable to exploit innovative and convenient methods for the rapid construction of isocoumarins.…”
Section: Introductionmentioning
confidence: 99%